2016
DOI: 10.1002/acr.22693
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Pain and Physical Functioning in Patients With Knee Osteoarthritis: A Systematic Review and Meta‐Analysis

Abstract: Objective. To systematically summarize the literature on the course of pain in patients with knee osteoarthritis (OA), prognostic factors that predict deterioration of pain, the course of physical functioning, and prognostic factors that predict deterioration of physical functioning in persons with knee OA. Methods. A search was conducted in PubMed, CINAHL, Embase, Psych-INFO, and SPORTDiscus up to January 2014. A meta-analysis and a qualitative data synthesis were performed. Results. Of the 58 studies include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
81
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 74 publications
9
81
1
9
Order By: Relevance
“…However, there were no significant differences between patients who completed the follow-up study and those who did not in baseline characteristics, which might indicate that data are missing at random. We confirmed that baseline knee pain intensity, which is a previously reported prognostic factor for worsening pain and disability [41], did not differ between completer and non-completer. Another important limitation is the small sample size, as the study might not have sufficient statistical power to detect a potential association between presence of PFOA and clinical outcome changes, particularly in patients with isolated medial PFOA.…”
Section: Discussionsupporting
confidence: 88%
“…However, there were no significant differences between patients who completed the follow-up study and those who did not in baseline characteristics, which might indicate that data are missing at random. We confirmed that baseline knee pain intensity, which is a previously reported prognostic factor for worsening pain and disability [41], did not differ between completer and non-completer. Another important limitation is the small sample size, as the study might not have sufficient statistical power to detect a potential association between presence of PFOA and clinical outcome changes, particularly in patients with isolated medial PFOA.…”
Section: Discussionsupporting
confidence: 88%
“…1,2,4,11 In addition, limitations in activities could predict joint health deterioration, as demonstrated in patients with osteoarthritis. 12 The aim of this study was to describe changes in joint health over a 5-to 10-year follow-up and identify factors associated with joint health deterioration in adult patients with moderate or severe haemophilia.…”
mentioning
confidence: 99%
“…It was found that in Sankt Petersburg universities such diseases are 43%; in Ryazan -more than 19%; in Homel -less than 17%; in Ulyanovsk it does not exceed 15% [20]. Some scientists found that osteoarthritis (OA) of knee joint cover 20% of world population [32,33,53].…”
mentioning
confidence: 99%